The Impact of COVID-19 on the Cinema Industry (مجلة الواحات للبحوث والدراسات, 2023)
Abstract:The COVID-19 pandemic has had a significant impact on the filmmaking and cinema industry since the beginning of 2020. The closure of cinemas and the halting of production caused major production companies to suffer huge material losses. Filmmakers have had to adapt to new practices, including an increasing trend towards digital viewing platforms, social networks, and virtual festivals, which have been the best solution in light of the pandemic. The use of online media, including SVOD's visual viewing platforms, has also increased as a result of the pandemic. The current world of cinematography is contingent on filmmakers trying to adapt to these new practices imposed by the pandemic.Keywords: Cinema, Film, Cinema Industry, COVID-19ملخص:أثرت جائحة كوفيد- 19 على صناعة السينما والأفلام على المستوى العالمي، حيث تم إغلاق دور السينما وتوقّف الإنتاج مما أدّى إلى تكبّد الشركات الكبرى في هذا المجال خسائر مادية كبيرة. ولقد اضطرّ المخرجون إلى التكيّف مع ممارسات جديدة بسبب الجائحة، مثل الإقبال على منصات العرض الرقمية، وشبكات التواصل الإجتماعي، والمهرجانات الإفتراضية، والتي كانت الحل الأمثل في ظل الجائحة. كما ازداد استخدام وسائل الإعلام عبر الإنترنت، بما في ذلك منصات العرض المرئي SVOD، نتيجة للجائحة. وأصبح العالم الحالي للسينما يعتمد على قدرة المخرجين على التكيّف مع هذه الممارسات الجديدة التي فرضتها الجائحة.كلمات دالة: السينما، الفيلم، الصناعة السينمائية، كوفيد-19